Evolusi Hukum Islam di Indonesia: dari Masa Kerajaan Islam hingga Era Reformasi - Sayyid Syahdan Almahdali; Abd. Rahman R; Qadir Gassing (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of Islamic law in Indonesia represents a significant phenomenon reflecting the dynamic interaction between religious values, the national legal system, and the country’s socio-cultural context. The urgency of this research lies in the need to understand how Islamic law has adapted and transformed throughout Indonesia’s multicultural and pluralistic history. The main objective of this study is to analyze the evolution of Islamic law from the era of Islamic kingdoms to the post-reformation period, as well as to assess its contribution to the modern national legal system. This study employs a qualitative descriptive method, using library research as the primary data collection technique, supported by content analysis of legal documents, academic literature, and historical records. The findings reveal that Islamic law in Indonesia has undergone a gradual process of integration—from a marginal position toward formal recognition within the national legal framework—aligned with the nation’s political and social transformations. This research contributes to strengthening the theory of legal integration and offers new insights into the relevance of Islamic law as a living law within the framework of Pancasila-based legal pluralism. In conclusion, Islamic law holds significant potential in shaping a fair and contextually grounded national legal system; however, further empirical research is needed to evaluate its practical implementation in contemporary socio-legal contexts.